An end-to-end model framework for understanding and predicting changes in Antarctic marine ecosystems - Ilari Stollberg; Sophie Bestley; Andrew Constable; Elizabeth A. Fulton; Javier Porobic; David Green; Denise O’Sullivan; Mao Mori; Stuart Corney; Michael Sumner; Jessica Melbourne-Thomas (Ecological Modelling, 2026)

Digital technologies and the study of adaptation in small-scale fisheries - Juan Carlos Villaseñor-Derbez; Rebeca Fernández; Stuart Fulton; Arturo Hernández-Velasco; Tamara Hernández; C. Brock Woodson; Juan Camilo Cárdenas; Giulio A. DeLeo; Jorge Torre; Fiorenza Micheli (Ocean & Coastal Management, 2026)

Small-scale fisheries in ecologically sensitive areas in Latin America and the Caribbean: Do marine protected areas benefit fisheries governance? - Ana Cinti; Luisa Ramirez; Mauricio Castrejón; Jaime A. Aburto; Luciana Loto; Stuart Fulton; Mario Rueda; Alexandre Schiavetti; Francisco J. Fernández-Rivera Melo; Manuel Bravo; Daniela Trigueirinho Alarcon; Valéria Penchel Araújo; et al. (Ambio, 2025)
Many small-scale fisheries (SSFs) in Latin America and the Caribbean (LAC) operate in ecologically sensitive areas, where balancing conservation and resource use is challenging. 'Multiple-use' marine protected areas (MPAs) have been implemented to accommodate SSFs (among other uses) within areas designated for conservation, creating opportunities and challenges for SSF governance. We analyzed eleven case studies from LAC to explore: (1) how different MPA institutional designs affect key aspects of SSF governance and (2) the links between these effects and the type of initiative that promoted MPA establishment (origin). Results indicate that the existence of an MPA benefited SSF governance in many ways, with more pronounced positive effects in MPAs with mixed to bottom-up origin supported by well-organized fishing groups. In addition, the presence of supportive MPA authorities that leveraged local capacities and initiatives and adopted flexible and collaborative governance systems made a difference in several cases. Lessons for integrating MPA and SSF governance are drawn.

Combining the uncombinable: corporate memories, ethnobiological observations, oceanographic and ecological data to enhance climatic resilience in small-scale fisheries - Isabel Garibay-Toussaint; Carolina Olguín-Jacobson; C. Brock Woodson; Nur Arafeh-Dalmau; Jorge Torre; Stuart Fulton; Fiorenza Micheli; Ryan O’Connor; Magdalena Précoma-de la Mora; Arturo Hernández-Velasco; Nemer E. Narchi (Frontiers in Marine Science, 2024)
The global food production system is increasingly strained by abrupt and unpredictable weather events, which hinder communities' ability to adapt to climate variations. Despite advances in meteorological predictions, many communities lack the academic knowledge or infrastructure to interpret these complex models. This gap highlights the need for solutions that make climate forecasts more accessible and actionable, especially for communities reliant on natural resources. This study explores the potential of enhancing seasonal climate forecasts by integrating local ecological knowledge (LEK) with scientific data. Specifically, we combined ethnobiological information gathered between 2022 and 2024 with existing oceanographic and ecological data to create an ethnobiological calendar for four fishing cooperatives. An ethnographic approach was used to understand the population's ethnobiological knowledge and their perceptions of marine heatwaves and climate change impacts. Coastal monitoring data was collected using moorings that recorded temperature over a 14-year period (2010–2024). To characterize giant kelp dynamics, we used an existing dataset of multispectral Landsat images, which estimates the surface canopy biomass of giant kelp forests. Ecological monitoring was conducted annually every summer from 2006 to 2023 to record the in situ abundance of ecologically and economically important invertebrate and fish species. Combining oceanographic, ecological, and ethnographic data, allowed for alligning fishers' observations with recorded marine heatwave events and ecological shifts. Our findings revealed that these observations closely matched documented marine heatwave data and corresponding ecological changes. The integration of LEK with scientific oceanographic data can significantly improved our understanding of dynamic climate regimes, offering contextually relevant information that enhances the reliability and utility of seasonal climate forecasts. By incorporating yearly data into an ethnobiological calendar, we promote more inclusive, community-based approaches to environmental management, advocating for the integration of LEK in climate adaptation efforts, emphasizing its crucial role in strengthening resilience strategies against climatic shocks.

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

Biomass accrual benefits of community-based marine protected areas outweigh their operational costs - Juan Carlos Villaseñor-Derbez; Stuart Fulton; Arturo Hernández-Velasco; Imelda G. Amador-Castro (Frontiers in Marine Science, 2023)
The costs and benefits of customary top-down Marine Protected Areas (MPAs) have been studied at length. But the costs and benefits of community-based MPAs –an increasingly common tool in conservation and fisheries management– remain understudied. Here, we quantify the operational costs of maintaining community-based MPA monitoring programs in nine small-scale fishing communities in Mexico. We then compare these costs to the potential extractive use value of invertebrate and fish biomass contained in the reserves. We find that the annual monitoring costs (median: 1,130 MXN/ha; range: 23-3,561 MXN/ha) represent between 0.3% and 55% of the extractive use value of the biomass contained in the reserves (median: 21.31 thousand MXN/ha; 5.22 - 49/12 thousand MXN/ha). These results suggest that the direct monetary benefits of community-based marine conservation can outweigh the costs of monitoring programs, providing further support for these types of management schemes. While further research should explore other mechanisms that would allow fishers to leverage the non-extractive use value of reserves ( e.g. , tourism) or the non-use value ( i.e. existence value of biodiversity) to sustainably finance their conservation efforts, a stop-gap measure to ensuring long-term monitoring costs are covered might include limited extractive use of resources contained in the reserves.

Two Decades of Community-Based Marine Conservation Provide the Foundations for Future Action - Juan Carlos Villaseñor-Derbez; Imelda G. Amador-Castro; Arturo Hernández-Velasco; Jorge Torre; Stuart Fulton (Frontiers in Marine Science, 2022)
As a member of the “High Level Panel for a Sustainable Ocean Economy”, Mexico has committed to expand community-based marine conservation. We draw from more than two decades of experience to outline how existing resources may be leveraged to help inform the country’s ambitious conservation plans. A total of 514.12 km 2 have already been protected under community-based marine reserves. 14 years of ecological survey data, more than 130 community surveyors, more than one hundred publications, and an entire digital infrastructure provide a solid platform on which to continue building the community-based marine conservation movement. Parallel and complimentary efforts have advanced regulation, action, data access and transparency, and coordination. Future interventions should innovate, but leverage existing resources and continue to involve communities.

Integrating Biophysical, Socio-Economic and Governance Principles Into Marine Reserve Design and Management in Mexico: From Theory to Practice - Magdalena Précoma-de la Mora; Nathan J. Bennett; Stuart Fulton; Adrian Munguia-Vega; Cristina Lasch-Thaler; Mariana Walther-Mendoza; José Alberto Zepeda-Domínguez; Elena Marie Finkbeiner; Alison L. Green; Alvin Suárez; Amy Hudson Weaver; Ana Luisa R. Figueroa Carranza; et al. (Frontiers in Marine Science, 2021)
Marine conservation design and fisheries management are increasingly integrating biophysical, socio-economic and governance considerations. Integrative approaches are adopted to achieve more effective, equitable, inclusive, and robust marine policies and practices. This paper describes a participatory process to co-produce biophysical, socio-economic, and governance principles to guide the design and management of marine reserves in three regions of Mexico: the Pacific region of the Baja California Peninsula, the Gulf of California, and the Mexican Caribbean. The process of co-producing the principles included convening a coordination team, reviewing the science, convening multi-stakeholder workshops, developing and communicating the principles with key practitioners and policy makers, and supporting uptake and application to policy and practice. Biophysical principles were related to: habitat representation and risk spreading; protecting critical, special and unique areas; incorporating connectivity; allowing time for recovery; adapting to changes in climate and ocean chemistry; and considering threats and opportunities. Socio-economic principles focused on: integrating the social context, local aspirations, and human-environment interactions; considering economic and non-economic uses, promoting an equitable distribution of costs and benefits, and respecting and maintaining cultural identity and diversity. Governance principles prioritized establishing and ensuring legitimacy and institutional continuity; implementing collaborative and adaptive management; and, promoting effective management. The paper also examines early efforts to implement the principles, next steps to promote further uptake and application in Mexico, and lessons learned from the process. Thus it provides insights into a practical process and a set of principles that are valuable to inform marine conservation and fisheries management processes elsewhere.

Trying to collapse a population for conservation: commercial trade of a marine invasive species by artisanal fishers - Luis Malpica-Cruz; Stuart Fulton; Anastasia Quintana; Jose Alberto Zepeda-Domínguez; Blanca Quiroga-García; Lizbeth Tamayo; Jose Ángel Canto Noh; Isabelle M. Côté (Reviews in Fish Biology and Fisheries, 2021)

Analytical and Computational Advances, Opportunities, and Challenges in Marine Organic Biogeochemistry in an Era of “Omics” - Andrew D. Steen; Stephanie Kusch; Hussain A. Abdulla; Nevenka Cakić; Sarah Coffinet; Thorsten Dittmar; James M. Fulton; Valier Galy; Kai-Uwe Hinrichs; Anitra E. Ingalls; Boris P. Koch; Elizabeth Kujawinski; et al. (Frontiers in Marine Science, 2020)

Untapped Potential of Citizen Science in Mexican Small-Scale Fisheries - Stuart Fulton; Catalina López-Sagástegui; Amy Hudson Weaver; Fernanda Fitzmaurice-Cahluni; Carlos Galindo; Francisco Fernández-Rivera Melo; Silvia Yee; María Belén Ojeda-Villegas; David Antonio Fuentes; Elizabeth Torres-Bahena (Frontiers in Marine Science, 2019)

A case for redefining the boundaries of the Mesoamerican Reef Ecoregion - Iliana Chollett; Lysel Garavelli; Daniel Holstein; Laurent Cherubin; Stuart Fulton; Stephen J. Box (Coral Reefs, 2017)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.